Política de educação e a gestão escolar no ensino médio: uma análise da implementação do ensino em tempo integral nas escolas públicas sergipanas - Sales, Natasha Ribeiro de Santana (2024)
Since the 1988 Federal Constitution, education has become a priority and a duty of both the state and the family. Authors such as Sylvester (1994) and Lück (2009) highlight the importance of education for accessing social rights and developing critical thinking. Secondary education has been the focus of discussions regarding educational policies, with the 1996 Education Guidelines and Basis Law (LDB) defining basic education and the recent 2017 Secondary Education Reform (REM) promoting significant changes. The REM aims to improve the quality of education and make it more attractive in response to the high dropout and failure rates. The National Education Plan (PNE) and the Program to Promote Full-Time Secondary Schools (EMTI) are some of the government’s actions to achieve the goals of universalizing education and expanding full-time education. Sergipe has joined the EMTI initiative. In this context, school management is crucial, involving the planning, execution, and evaluation of educational actions, as well as the creation of a school environment that encourages student engagement and success. It must include, in addition to administrative aspects, pedagogical practices that adapt to students’ needs. Comprising both administrative and pedagogical dimensions, the coordination of these efforts, as revealed by the research conducted, proved to be complex due to political and organizational factors. This research, therefore, explores the implementation of Full-Time Secondary Education (EMTI) in Sergipe, investigating how school management operates in both the pedagogical and administrative dimensions. The study is justified by the importance of EMTI in preparing young people for academic life and the job market, as well as the need for research on its implementation in Sergipe, where educational policy is recent and has been little addressed. To this end, it is based on works by authors such as Lück (2001; 2009; 2011), Cavaliere (2002; 2007; 2010), Lotta (2018; 2021), and others who discuss school management and public policies. The main objective is to understand the role of school management in the implementation of EMTI, which is broken down into the following specific objectives: to analyze the performance of school professionals and to describe pedagogical and administrative management practices. The methodology employs a qualitative approach, featuring a case study in two schools that involves semi-structured interviews with managers, coordinators, teachers, and school secretaries. Thus, this study highlights the importance of school management for the effective implementation of actions and the fulfillment of objectives within schools, with an emphasis on collaboration among managers, coordinators, secretaries, and teachers. It is concluded that school management is fundamental to the successful implementation of EMTI and that aligning pedagogical and administrative practices with educational policies is necessary to achieve better results.